Patient perceptions of anticoagulant treatment with dabigatran or a vitamin K antagonist for stroke prevention in atrial fibrillation according to region and age: an exploratory analysis from the RE-SONANCE study - Vinereanu, Dragos; Napalkov, Dmitry; Bergler-Klein, Jutta; Benczur, Bela; Ciernik, Martin; Gotcheva, Nina; Medvedchikov, Alexey; Põder, Pentti; Simić, Dragan; Skride, Andris; Tang, Wenbo; Trusz-Gluza, Maria; et al. (Journal of thrombosis and thrombolysis, 2021)
BACKGROUND: The oral anticoagulant dabigatran offers an effective alternative to vitamin K antagonists (VKAs) for stroke prevention in atrial fibrillation (AF), yet patient preference data are limited. The prospective observational RE-SONANCE study demonstrated that patients with AF, newly initiated on dabigatran, or switching to dabigatran from long-term VKA therapy, reported improved treatment convenience and satisfaction compared with VKA therapy. This pre-specified sub-study aimed to assess the impact of country and age on patients' perceptions of dabigatran or VKA therapy in AF. METHODS: RE-SONANCE was an observational, prospective, multi-national study (NCT02684981) that assessed treatment satisfaction and convenience in patients switching from VKAs to dabigatran (Cohort A), or newly diagnosed with AF receiving dabigatran or VKAs (Cohort B), using the PACT-Q questionnaire. Pre-specified exploratory outcomes: variation in PACT-Q2 scores by country and age (< 65, 65 to < 75, ≥ 75 years) (both cohorts); variation in PACT-Q1 responses at baseline by country and age (Cohort B). RESULTS: Patients from 12 countries (Europe/Israel) were enrolled in Cohort A (n = 4103) or B (n = 5369). In Cohort A, mean (standard deviation) PACT-Q2 score increase was highest in Romania (convenience: 29.6 [23.6]) and Hungary (satisfaction: 26.0 [21.4]) (p < 0.001). In Cohort B, mean (standard error) increase in PACT-Q2 scores between dabigatran and VKAs was highest in Romania (visit 3: 29.0 [1.3]; 24.5 [0.9], p < 0.001). Mean PACT-Q2 score increase by age (all p < 0.001) was similar across ages. PACT-Q1 responses revealed lowest expectations of treatment success in Romania and greatest concerns about payment in Estonia, Latvia, and Romania, but were similar across ages. CONCLUSIONS: Treatment satisfaction and convenience tended to favor dabigatran over VKAs. Regional differences in treatment expectations exist across Europe. TRIAL AND CLINICAL REGISTRY: Trial registration number: ClinicalTrials.gov NCT02684981. Trial registration date: February 18, 2016.
Keywords: fibrinolytika; Administration, Oral; vitamin K; Non‐vitamin K antagonist oral anticoagulant; antikoagulancia; Fibrinolytic Agents; Stroke prevention; aplikace orální; cévní mozková příhoda; Dabigatran; Stroke; Aged; Prospective Studies; senioři; dabigatran; Warfarin; Atrial Fibrillation; lidé; Vitamin K; Anticoagulants; Humans; Atrial fibrillation; Patient perception; lidé středního věku; fibrilace síní; Middle Aged; prospektivní studie